A “Era de Ouro” da Loose Moose Theatre Company: A formação e perpetução da companhia através da pedagogia de Keith Johnstone - Dudeck, Theresa Robbins (2015)
Keith Johnstone, the groundbreaking teacher, theorist, and creator of improvisational theatre practices, founded the Loose Moose Theatre Company in Calgary in 1977 to showcase impro and an ambitious season of plays, many written by Johnstone himself. Johnstone’s Theatresports was the vehicle that catapulted impro and the Loose Moose onto the world stage in the early 1980s— the “Golden Era.” But as Johnstone began to withdraw from the artistic director position, Loose Moose’s reputation as an innovative, radical theatre company declined. Why? This paper explores Johnstone’s pedagogy and how it influenced the formation and perpetuation of the Loose Moose during its “Golden Era.”